Kepastian Hukum Pemenuhan dan Perlindungan Hak-Hak Pedagang Kaki Lima (Studi di Pasar Tradisional Sila Kabupaten Bima) - Munir; Nasrullah; Diniyatun Islami (Jurnal Hukum Lex Generalis, 2025)
This study examines legal certainty in the fulfillment and protection of street vendors' rights at the Traditional Market of Sila, Bima Regency. Using a juridical-sociological approach, the findings reveal that although vendors' basic rights are normatively recognized, their implementation remains weak due to the lack of technical regulations and firm local governance. The study concludes that strengthening local regulations and law enforcement roles is essential to ensuring real protection for street vendors.